Development of a scale assessing Beliefs About ThirdHand Smoke (BATHS). Issue 1 (December 2017) - Haardörfer, Regine; Berg, Carla; Escoffery, Cam; Bundy, Łucja; Hovell, Melbourne; Kegler, Michelle
Abstract Background Similarly to secondhand smoke (SHS), thirdhand smoke (THS) beliefs may be correlated with smoking behaviors and smokefree policies in the home. Thus, there is a need to develop and validate measures to assess beliefs about THS. Methods A list of 19 items related to THS were generated by an expert panel and tested in a pilot study. Based on results from an exploratory factor analysis, two factors emerged: THS persistence in the environment and THS impact on health. The scale was reduced to nine items, which showed no differential item functioning by smoking status or smoking ban status in the home. The nine items and the two factor structure were tested in a validation sample from a smoke-free homes intervention that included THS educational materials. Results The 9-item scale showed excellent internal consistency. Confirmatory factor analysis indicated good model fit for the two factor solution in a low-income population. Tests of construct validity indicated differences due to exposure to the smoke-free homes intervention, by smoking status, whether participants own or rent their home, and smoking ban status in the home. Conclusions The BATHS scale offers researchers a valid and reliable tool to assess THS beliefs.